Combating Air Pollution through Data Generation and Reinterpretation: Community Air Monitoring in Taiwan. Issue 2 (1st June 2019) - Tu, Wen-Ling
Abstract: Although cities in Taiwan are not as choked by smog as Beijing or Delhi, where people can hardly enjoy blue skies, air pollution is still a serious problem and has repeatedly aroused social concerns in central and southern Taiwan since 2010. Unsatisfied with the government's passive responses, the citizen groups in Taiwan have initiated several air monitoring projects to develop air-pollution claims and contest the deficiencies of the official air-pollution standard, data, and regulatory actions. Inspired by the concept of social movement–based citizen science, this article discusses how local community people have participated in knowledge production by integrating their observations and experiences into the scientific practices of air monitoring. The discussions particularly address citizens' data generation and interpretation efforts that signaled the alternative air quality information and triggered on-demand responses from the government to improve the air quality management measures. The analysis further highlights the characteristics of community air monitoring in Taiwan as well as its potentials and limitations.